Social skills in Study Groups at the Faculty of Veterinary Sciences of the Universidad Nacional del Litoral (Esperanza, Santa Fe, Argentina) - Báez, María Ludmila (2020)
To access a good job offer the person must be trained for it and the University is one of the main pillars to meet this requirement, although the curriculum must be complemented with other aspects such as the development of social skills. A study group must possess basic social skills such as teamwork, empathy, communication and leadership, among others. The objectives of this research were to socialize among the members of each Study Group directed by the Faculty of Veterinary Sciences the conditions that identify a team, describe from the own perception of the members of each group their social skills to integrate the group and the difficulties for it to become a team, and also to conduct a survey to understand their opinions. It can be concluded that there is a greater appreciation of the perception of teamwork in functional groups. It is evident the need to design a special program by educational institutions where they commit to the task of implementing instances of teamwork and interaction spaces to improve communication to generate, not only successful professionals in the scientific-technical, but also socially and emotionally, which will result in a professional capable of effectively interacting with the community.